The Influence of Village Apparatus Competence, Individual Morality and Internal Control System on Fraud Prevention in Village Fund Management - Ayem, Sri; Pratiwi, Asih Fajar (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Villages are government organizational units that deal directly with communities with diverse background interests and needs and have a very important role. This research aims to analyze the influence of village apparatus competence, individual morality and internal control systems on preventing fraud in managing village funds. The sampling technique used in this research was purposive sampling, so that 135 samples were obtained using the questionnaire method. This research derives three hypotheses for each part of Village Apparatus Competency, Individual Morality, Internal Control Systems. The result of this research show that the competence of village officials has no effect on preventing fraud in managing village funds. The results of the hypothesis test show that the value of the village apparatus competency variable is significant. Individual morality has a positive effect on preventing fraud in village fund management. The internal control system has a positive effect on preventing fraud in village fund management.